P‐Type Boron‐Doped Monolayer Graphene with Tunable Bandgap for Enhanced Photocatalytic H 2 Evolution under Visible‐Light Irradiation - Wu, Yujun; Han, Zhanli; Younas, Waqar; Zhu, Youqi; Ma, Xilan; Cao, Chuanbao (ChemCatChem, 2019)
Graphene‐based materials are considered as one of the promising photocatalysts for hydrogen production from solar‐driven water splitting yet subject to zero bandgap limitation. Here, we report an efficient one‐step pyrolysis for preparing p‐type boron‐doped monolayer graphene. Through varying the dopant content, the bandgap of the boron‐doped graphene can be tuned. Moreover, a p‐type conductivity behavior of the boron‐doped monolayer graphene is demonstrated by the four‐probe measurement and Hall effect measurement. The boron‐doped graphene can service as an efficient semiconductor photocatalyst for hydrogen production from water splitting under visible‐light irradiation. The optimized boron‐doped graphene can deliver a high H 2 production rate of 219.3 μmol h −1 g −1 without any cocatalyst. The photocatalyst can be recycled at least four times without obvious activity decay and maintain high H 2 production rate of 215.3 μmol h −1 g −1 after 60 h reaction, indicative of excellent stability. This work may open up a new avenue for fabrication of new photocatalysts based on p‐type boron‐doped monolayer graphene.